(untitled) (PANGEEA, 2025)
Our reason to focus the research on the national system of child social protection in Romania is to underline the fact that this category of subjects is the most vulnerable and at risk from social categories in our country. To underline the subject of research, we will highlight some key terms that are directly related to the subject. The term "child", in the social assistance specific legislation, is defined according to the law and legal provisions referred to. Thus, Law no. 272/2004, on the Protection and Promotion of the Rights of the Child defines in Article 4(a.) as a "child - a human being below the age of 18, who has not acquired full capacity of exercise, according to the law."